PARATHYROID CARCINOMA: CURRENT STATE OF KNOWLEDGE AND LITERATURE REVIEW - Anna Barbara Tuleja; Julia Kosmulska; Jakub Nowak; Michał Drabik; Mateusz Kęska; Michael Platschek; Klaudia Dybalska; Maksym Sikora; Karol Józef Szkarłat; Sylwia Wiktoria Kolano (International Journal of Innovative Technologies in Social Science, 2025)
Parathyroid carcinoma (PC) is a rare malignancy of the parathyroid glands, accounting for only a minute fraction of all cancers worldwide. Although uncommon, it poses significant diagnostic and therapeutic challenges because its clinical features often resemble those of benign primary hyperparathyroidism (PHPT). This review summarizes current understanding of PC, integrating recent advances in epidemiology, genetics, diagnostics approaches and management. The global incidence is estimated at 3–6 new cases per 10 million people annually, affecting men and women equally and typically presenting around the fifth decade of life. Genetic alterations play a central role in pathogenesis. Mutations in CDC73 with consequent loss of parafibromin function are the most characteristic finding, especially in the hereditary hyperparathyroidism–jaw tumor (HPT-JT) syndrome. Other hereditary conditions such as multiple endocrine neoplasia types 1 and 2 (MEN1 and MEN2) or isolated familial hyperparathyroidism may also involve the parathyroid glands, though carcinoma remains rare in these syndromes. Additional molecular abnormalities, such as alterations in RB1, TP53, BRCA2, and CCND1, and activation of PI3K/AKT-/mTOR and MAPK pathways - have been linked to tumor progression. The cornerstone of treatment is early, complete en bloc resection, offering the best chance of cure. For recurrent or metastatic disease, therapy focuses on controlling hypercalcemia using cinacalcet, denosumab, and, in selected cases, adjuvant radiotherapy. Early recognition, genetic testing, and multidisciplinary care are crucial for improving long-term outcomes in this rare but challenging endocrine malignancy.